Synthesis of Calcium Phosphate from Cockle Shell Loaded by Silver Nanoparticle and Its Antibacterial Activity Evaluation - Yuant Tiandho; Rahmad Lingga; Evi.J Evi.J; Rifqi Almusawi Rafsanjani; Fitri Afriani (Indonesian Review of Physics (IRiP), 2021)
This study aimed to synthesize calcium phosphate loaded with silver nanoparticles and evaluate its antibacterial activity. We used cockle shells waste as raw material to prepare calcium phosphate. X-ray diffraction analysis showed that the constituent phases of calcium phosphate consist of hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP). The incorporation process of silver nanoparticles on calcium phosphate was carried out in colloidal silver nanoparticles via the green-synthesis method using Citrus x microcarpa Bunge peel extract. The presence of colloidal silver nanoparticles through the green synthesis method was identified using UV-Vis spectrophotometer by the peak of the absorption band that occurred at 468 nm. The incorporation of silver nanoparticles into calcium phosphate did not significantly change the crystalline properties of HA and β-TCP. Evaluation of the antibacterial activity showed the silver nanoparticles had a strong antibacterial effect against Staphylococcus aureus, which also occurs in calcium phosphate loaded by silver nanoparticles. After being incorporated with silver nanoparticles, Calcium phosphate generally has no antibacterial effect. After being incorporated with silver nanoparticles, an inhibition zone with a diameter of about 9.8 mm can form. These results indicated that the method proposed in this study could be an alternative for developing calcium phosphate, which requires self-sterilization properties.